Allele and genotype frequencies for primary hereditary cataract, multifocal retinopathy 1, and degenerative myelopathy in Pyrenean Mountain dog from Italy - R. Moretti; G. Massimello; S. Chessa; S. Sartore; A. Tranchero; M. Profiti; P. Sacchi (Topics in Companion Animal Medicine, 2024)

First detection of Mnemiopsis leidyi (Ctenophora, Bolinopsidae) in Sardinia (S’Ena Arrubia Lagoon, Western Mediterranean): a threat for local fishery and species recruitment - R. DICIOTTI; J. CULURGIONI; S. SERRA; M. TRENTADUE; G. CHESSA; C. T. SATTA; T. CADDEO; A. LUGLIE; N. SECHI; N. FOIS (Mediterranean Marine Science, 2016)
The invasive comb jelly Mnemiopsis leidyi is a lobate ctenophore native of coastal and estuarine waters of the temperate western Atlantic Ocean. In the last decades this species has expanded its range of distribution, colonizing marine and transitional environments in Europe. In October 2015, during a survey fishing the European eel Anguilla anguilla in Sardinia (western Mediterranean), a massive bloom of this specie was observed in the eutrophic S’Ena Arrubia Lagoon for the first time. In November 2015, sampling was conducted at three stations in the lagoon and in a fyke net, in order to estimate the abundance of M. leidyi and to determine its impact on the fishing activity. The results showed an abundance of 2.83 ctenophores m-3. Specimens were all adults, measuring 18 - 62 mm total length. The abundant number of ctenophores (6837 individuals per fyke net) damaged fishing operations, reducing catches and affecting the performance of fishing gears. Since there is no effective mechanical, chemical or biological method to counter M. leidyi, the short term economic damage may be approached by new management measures of fisheries. In addition, other actions against the recurring of M. leidyi invasion, can include management strategies, in particular those finalized to reduce the high trophic state of the lagoon.

Human impact on Paracentrotus lividus: the result of harvest restrictions and accessibility of locations - G. Ceccherelli; A. Pais; S. Pinna; N. Sechi; L. A. Chessa (Marine Biology, 2011)

Molecular Cloning and Expression of a Surface Lipoprotein of Mycoplasma Capricolum as a Potential Antigen for Serological Diagnosis - P. Robino; A. Alberti; B. Chessa; M. Pittau; M. Profiti; S. Rosati (Veterinary Research Communications, 2007)

Perspectives for development of low impact aquaculture in a Western Mediterranean lagoon: the case of the carpet clam Tapes decussatus - L.A. Chessa; F. Paesanti; A. Pais; M. Scardi; S. Serra; L. vitale (Aquaculture International, 2005)

Mesoscale Precipitation and Temperature Regimes in Sardinia (Italy) and their Related Synoptic Circulation - P. A. Chessa; D. Cesari; A. M. S. Delitala (Theoretical and Applied Climatology, 1999)

Objective analysis of daily extreme temperatures of Sardinia (Italy) using distance from the sea as independent variable - Piero A. Chessa; Alessandro M. S. Delitala (International Journal of Climatology, 1997)

Objective analysis of daily extreme temperatures of Sardinia (Italy) using distance from the sea as independent variable - Piero A. Chessa; Alessandro M. S. Delitala (International Journal of Climatology, 1997)